Application of Istishna to buying and selling furniture (case study of Sambi Tereng gallery shop) - Amelia Jannati, Rizka; Ahmad Amir Aziz; Muhammad Azkar (Faculty of Islamic Economics and Business UIN Salatiga, 2024)
This study aimed to determine the application of istishna' in buying and selling furniture at the Sambi Tereng Gallery Shop. The approach used in this research is a qualitative approach which produces descriptive data. Data collection techniques in this research used observation, interviews and documentation. The informants in this research consisted of 1 key informant, 3 main informants, and 3 additional informants. The technique for checking the validity of the data used by the author in this research was the triangulation technique. The results of this research show that the application of istishna' in buying and selling furniture at the Sambi Tereng Gallery Shop has been applicated in accordance with the pillars and requirements of istishna'.